NITROGEN RESPONSE AND 15N-LABELLED FERTILISER RECOVERY BY HOOP PINE SEEDLINGS GROWN UNDER GLASSHOUSE CONDITIONS - K A. Bubb (Journal of Tropical Forest Science (JTFS), 2022)
This study was undertaken in response to the need to determine whether hoop pine (Araucaria cunninghamii) seedlings established on second rotation (2R) soils will benefit from nitrogen (N) fertilisation if applied in combination with a range of soil surface cover conditions. A trial was established under glasshouse conditions testing in factorial arrangement, 2 contrasting soils (low and average site productivity), 4 soil cover treatments (litter cover, cover crop consisting of kikuyu, ash cover and bare soil), and 6 N-fertiliser treatments (5 rates of inorganic-N fertiliser and a N-fixing legume). The treatments were replicated 3 times and laid out in a completely randomised factorial with 5 rates of inorganic-N fertiliser applied as ammonium sulphate at 0,167, 333,500 and 667 mg N kg-1dry soil. The 333 mg N kg-1 treatment received 15N-labelled ammonium sulphate. The N-fixing legume was Wynn’s cassia (Cassia rotundifolia). The seedling growth response for the experimental period of 7 months was significantly higher on the average site productivity plantation soil than that on the low site productivity soil. There was a significant difference between the cover treatments in height and diameter at ground level (DGL) with the order of response being litter > ash = bare > cover crop. No significant growth responses by the hoop pine seedlings to the inorganic-N fertiliser treatments were observed. There was no evidence that the legume treatment had increased the soil-N status. Significant differences between the cover treatments with respect to the total recovery of the l5N-labelled fertiliser were noted. The litter cover and bare soil treatments had the highest 15N recovery from the soil-plant system of 96%, compared with 84% for the cover-crop treatment and 63% for the ash treatment. Both the legume and the kikuyu cover crop severely restricted the growth of the hoop pine seedlings. The implications of applying N fertilisers to young hoop pine seedlin gs at plantation establishm ent and potential N loss mechanisms are discussed.